Energy Efficiency and Energy Demand: Structural Analysis of Rebound Effects - (:unkn) unknown (My University, 2025)
The rebound effect refers to the behavioral or other systemic responses to new technologies that increase the efficiency of resource use. These responses tend to offset the beneficial effects of the new technology. In particular the rebound effect to energy efficient technologies has a crucial role in identifying energy demand and its evolution. Identification of the rebound effect is a challenging empirical problem because of endogeneity and self-selection issues regarding the adoption of technologies. To date, there is no comprehensive study of the rebound effect that roots empirical analysis to the economic theory. Moreover, despite the great importance of rebound effects in energy consumption there is little research based on micro-level data, addressing the endogeneity problem. In particular in the case of Switzerland there is hardly any economic research on the rebound effect. This study adopts a structural estimation approach for identifying the rebound effect in energy consumption. The structural model of energy demand will be based on a conceptual decision-making problem, including the adoption decision and the intensity of usage. The two decisions are made simultaneously hence requiring a simultaneous system of structural equations for the selection of efficiency level and the energy demand. While the structural approach will be based on similar models used in empirical industrial organization, we envisage alternative theoretical developments based on both standard and non-standard utility theory. In each case, a tractable econometric model will be derived based on the economic theory. We are notably interested in the role of heterogeneous preferences and consumer characteristics on the endogenous determinants of the rebound effect, as well as other mechanisms yielding indirect rebound effects. Additional information on the demand in other energy sectors collected at the micro level will enable us to characterize such indirect rebound effects. The analysis will be based on the available micro-level data as well as additional data that are planned to be collected. The collected data include household energy consumption as well as a choice experiment with hypothetical decisions about energy consumption and technology alternatives such as the type and energy efficiency of consumer durables used by the household. The developed structural econometric framework would enable us to relate the estimated parameters of the empirical model to the theory. The structural approach will be a strong potential contribution to the field of energy economics. With the developed models applied to household and aggregate data from Switzerland, we will achieve an important product of this research namely, the assessment of the rebound effects in energy demand of Swiss consumers. Here, we plan to focus at a first stage, on fuel consumption and cars, in which the available data allow a relatively quick analysis. The direct rebound effect in the transport sector as well as the indirect rebound effects in the overall energy demand will be examined in later stages using the household data. At the aggregate level, we will extend previous studies by estimating a simultaneous system of structural equations. We will introduce new econometric specifications with heterogeneous parameters and improve the identification strategy. The study will be completed by applying the proposed methods to data collected at the micro level and the outcomes of a choice experiment conducted among Swiss households. The collected micro-level data will be a unique basis not only for further research on potential rebound effects within and across different sectors but provide an empirical basis for the assessment of behavioral elements of consumers’ responses to energy efficient technologies. This research will also have significant policy implications. A better identification of the rebound effect would allow more refined policies with targeted efforts towards energy conservation. Finally, the proposed empirical study provides a basis for welfare analyses that can be used to assess the impact of various energy policies.
Keywords: Rebound effect; Energy efficiency; Structural estimations.